Intraoral Cellular Schwannoma Involving Maxillary Gingiva: A Rare Case Report - Sushilkumar Bagul; Sanjay Chandan; Narayan Dutt Pandey; Sneha H Choudhary (Tehran University of Medical Sciences, 2023)
Oral schwannomas (OSs) are uncommon benign nerve sheath tumors accounting for 1% of all schwannomas and may arise from either soft tissue or bone. Cellular schwannoma is a rare histological variant of schwannoma which is characterized by increased cellularity. The most common intraoral site of occurrence is the tongue followed by the floor of the mouth and palate. Here, we are reporting a rare case of intraoral cellular schwannoma involving both facial and palatal gingiva of the right maxilla in a young Indian male patient.